Prevalence and predictors of anxiety in an African sample of recent stroke survivors (2017)
Objectives: Studies considering emotional disturbances in the setting of stroke have primarily focused on depression and been conducted in high-income countries. Anxiety in stroke survivors, which may be associated with its own unique sets of risk factors and clinical parameters, has been rarely investigated in sub-Saharan Africa (SSA). We assess the characteristics of anxiety and anxiety-depression comorbidity in a SSA sample of recent stroke survivors. Materials and methods: We assessed baseline data being collected as part of an intervention to improve one-year blood pressure control among recent (≤1 month) stroke survivors in SSA. Anxiety in this patient population was measured using the Hospital Anxiety and Depression Scale (HADS), while the community screening instrument for dementia was used to evaluate cognitive functioning. Independent associations were assessed using logistic regression analysis. Results: Among 391 participants, clinically significant anxiety (HADS anxiety score≥11) was found in 77 (19.7%). Anxiety was comorbid with depression in 55 (14.1%). Female stroke survivors were more likely than males to have anxiety (OR=2.4, 95% CI=1.5-4.0). Anxiety was significantly associated with the presence of cognitive impairment after adjusting for age, gender and education (OR=6.8, 95% CI=2.6-18.0). Conclusions: One in five recent stroke survivors in SSA has clinically significant anxiety, and well over 70% of those with anxiety also have depression. Future studies will need to determine what specific impact post-stroke anxiety may have on post processes and outcomes.